Nutrient enrichment, propagule pressure, and herbivory interactively influence the competitive ability of an invasive alien macrophyte Myriophyllum aquaticum - Huang, Ru; Oduor, Ayub M. O.; Yan, Yimin; Yu, Weicheng; Chao, Chuanxin; Dong, Lei; Jin, Shaofei; Li, Feng (Frontiers in Plant Science, 2024)
Freshwater ecosystems are vulnerable to invasion by alien macrophyte species due to their interconnected nature and the various vectors . The release from specialized natural enemies should allow introduced species to allocate resources that would have been used for defense mechanisms towards greater growth and reproduction, leading to increased invasion success. However, our understanding of the interactive effects of propagule, herbivory, and nutrient enrichment on competitive interactions between invasive alien macrophytes and native macrophyte communities in freshwater ecosystems is limited due to a lack of studies. Here, we conducted a full factorial mesocosm experiment to examine the separate and potential interactive effects of herbivory, nutrient availability, propagule pressure, and competition on the invasion success of the alien macrophyte Myriophyllum aquaticum into a native macrophyte community consisting of Vallisneria natans, Hydrilla verticillate and Myriophyllum spicatum. We assembled a native macrophyte community of the three species, which we then invaded with M. aquaticum at low (one individual; low-propagule pressure) vs high (four individuals; high-propagule pressure) density and fully crossed with two levels of herbivory by a native snail Lymnaea stagnalis (with herbivory vs no-herbivory) and two levels of nutrient availability (low-nutrient vs high-nutrient). We also grew M. aquaticum separately at low and high density in the absence of competition from the native macrophyte communities. We hypothesized that: (1) the invasive alien macrophyte would have a significantly stronger competitive effect on the biomass of native macrophytes when the invader is introduced at higher density; (2) nutrient enrichment would enhance competitive effect of the alien macrophyte on the native macrophyte community, especially in the presence of herbivory. Results show that both the alien macrophyte M. aquaticum and the native macrophyte community experienced growth benefits from increased nutrient availability, although the effect of nutrient was modulated by propagule pressure in the case of native macrophyte communities and by competition, herbivory, and propagule pressure in the case of M. aquaticum. The significant influence of the four-way interaction among herbivory, nutrient availability, propagule pressure, and competition on the shoot biomass and total biomass of alien macrophytes suggests that the dynamics of invasion are multifaceted and context-dependent.